Los juegos recreativos y su influencia en las capacidades coordinativas en estudiantes de séptimo año paralelo C en la Escuela de Educación Básica ❝Miguel Riofrio” de la ciudad de Loja. - Ramón González, Cristian Giancarlo (2024)
This Curricular Integration Work was developed to evaluate recreational games and their influence on the improvement of the coordination capacities of orientation, reaction, dynamic balance, and static balance in 7th-grade students of General Basic Education, class C, of the Miguel Riofrio School of Basic Education in the city of Loja, period 2024. The type of study was descriptive correlational, with a quasi-experimental design. Diagnostic instruments such as a questionnaire and the orientation, reaction, dynamic balance, and static balance tests were applied to 31 students. According to the results obtained once the diagnostic instruments were used, it is evident that in the survey 58% know recreational games, and 48% practice recreational games with a frequency of two to three days a week. As for the pre-tests applied in the indicator equivalent to excellent, the following results were obtained: in the orientation test 26%, in the reaction test a result of 13% was obtained, in the dynamic balance test 26% to the indicator of excellent, and finally, in the static balance test a result of 19% equivalent to excellent was obtained. These results were not negative taking into account the rest of the indicators and sample, but with the possibility of improving in these aspects. Based on these results, an intervention program of recreational games was designed and applied, which was structured in 12 class sessions with recreational games focused on the different coordination capacities. Consequently, evaluation instruments were used, which in this case were the post-tests, to show the improvement in coordination skills, where the goal is to achieve that a large part of the sample reaches the excellent indicator. Key Words: Recreational games, special coordinative capacities, test, methodology, influence.